2007
DOI: 10.1590/s1517-83822007000200022
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in brazilian instant coffee

Abstract: The aim of this study was to determine the ochratoxin A (OTA) contamination of instant coffee samples collected in the market of the city of São Paulo, Brazil from August to December, 2004. The EN 14133/2003 method, originally developed to quantify OTA in wine, grape juice and beer samples, was evaluated and approved for analyzing OTA in instant coffee samples. OTA was isolated in an immunoaffinity column and quantified by HPLC with fluorescence detection. The established detection and quantification limits we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 13 publications
1
17
0
4
Order By: Relevance
“…Studies conducted in Brazil have shown that the percentage of coffee samples contaminated with OTA ranges from 7.5 % to 98.8 % and the OTA levels range from 0.10 to 7.30 ng/g and from 0.10 to >100 ng/g in green and processed coffee, respectively (Table 3) (Prado et al 2000;Taniwaki et al 2003;Batista et al 2003;Martins et al 2003;Gollücke et al 2004;Almeida et al 2007;Batista et al 2009). In coffee samples from Mexico, OTA occurrence were low and the OTA level detected on green coffee samples was 0.20 ng/g, while on processed coffee, samples varied between 0.10 and 0.30 ng/g (Suárez-Quiroz et al 2004).…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 99%
“…Studies conducted in Brazil have shown that the percentage of coffee samples contaminated with OTA ranges from 7.5 % to 98.8 % and the OTA levels range from 0.10 to 7.30 ng/g and from 0.10 to >100 ng/g in green and processed coffee, respectively (Table 3) (Prado et al 2000;Taniwaki et al 2003;Batista et al 2003;Martins et al 2003;Gollücke et al 2004;Almeida et al 2007;Batista et al 2009). In coffee samples from Mexico, OTA occurrence were low and the OTA level detected on green coffee samples was 0.20 ng/g, while on processed coffee, samples varied between 0.10 and 0.30 ng/g (Suárez-Quiroz et al 2004).…”
Section: Impact Of Ochratoxin a Production By Aspergillus Section Nigmentioning
confidence: 99%
“…After that, the IA column was washed with 10.0 mL of Milli-Q water at the same flow rate in green coffee of 15 ng.g -1 will result in a finished product that does not exceed the EU maximum limits (FOOD..., 2010). Several methods have been described for determining OTA in food matrix such as thin layer chromatography, spectrofluorometry, enzyme-linked immunosorbent assay, high performance liquid chromatography and liquid chromatography-mass spectroscopy (ALMEIDA et al, 2007;MASOUD;KALTOFT, 2006;PRADO et al, 2000;GILBERT;ANKLAM, 2002;PARDO et al, 2004;AHMED et al, 2007;SUGITA-KONISH et al, 2006). Reviewing the process it can be said that: the toxin is usually extracted with water, organic solvents, salt aqueous solution and acids or several mixtures.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…This mycotoxin has been found in food commodities such as cereals, oleaginous seeds, wine, meat, cocoa, spices, dried fruits, grapes, beer, green, roasted and instant coffee (ALMEIDA et al, 2007;BECKER et al, 1998;BRESH et al, 2000;BUCHELLI;TANIWAKI, 2002;BULLERMAN, 2003;FUJII et al, 2002FUJII et al, , 2007 potassium chloride (Merck,Germany,99.5%), potassium dichromate (Merck, Germany, 99.5%), sulfuric acid (Merck, Germany, 97.0%), methanol HPLC grade (Tedia, USA, 99.9%), trifluoroacetic acid HPLC grade (Tedia, USA, 99.8%), acetone pesticide grade (Tedia, USA, 99.8%), glacial acetic acid (Tedia, USA, 99.9%), toluene HPLC grade (Tedia, USA, 99.8%), benzene (Merck, Germany, 99.5%), acetone A.C.S. grade (Tedia, USA, 99.8%), ethyl alcohol (Quimes, Brazil, 95.0%), sodium hypochlorite (Invema, Brazil, 12.0%) and alcaline extran (Merck, Germany).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] This mycotoxin has been found in food commodities such as cereals, oleaginous seeds, wine, meat, cocoa, spices, dried fruits, grapes, beer, green, roasted and instant coffee. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Once OTA is formed, it survives in most of food-processing steps, such as cooking, fermenting and roasting, as in the case of coffee beans. Roasted coffee produces the most different results in terms of OTA stability, since losses were reported in the range of 0-100%.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Several techniques have been described for determining OTA in food matrix using thin-layer chromatography (TLC), gas chromatography (GC), enzyme-linked immunosorbent assay (ELISA), high performance liquid chromatography with fluorescence detector (HPLC-FLD) and liquid chromatography-mass spectroscopy (LC/ MS). 7,16,19,[28][29][30][31] The Official Methods of Analysis of AOAC International (AOAC) recomends a method for the determination of OTA is based on TLC and HPLC-FLD. Method proposed by Ministério da Agricultura, Pecuária e Abastecimento (MAPA) is based on HPLC--FLD.…”
Section: Introductionmentioning
confidence: 99%